PENERAPAN SANKSI HUKUM TERHADAP PELAKU PENJUAL MAKANAN YANG MENGANDUNG BAHAN BERBAHAYA OLEH BALAI BESAR PENGAWAS OBAT DAN MAKANAN BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2012 TENTANG PANGAN DI PEKANBARU - JERNI TARIDA SILITONGA; Evi Deliana; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
the purpose of this research is to find out what is behind the sale of selling foods containing hazardous materials, how is the legal arrangement regarding the sale of food containing hazardous materials by the Center for Food and Drug Supervisor based on Food Law in Pekanbaru, and how the application of criminal sanctions against food vendors who compare the hazardous substances by the Center for Food and Drug Supervisors under the Food Law.by using sociological law research methods, it can be concluded: 1. underlying the sale of foods containing hazardous materials is basically done in order to minimize product expenditure and generate the highest profits, without having to pay attention to public health, such as formaldehyde commonly used to preserve corpses, may be misused by traffickers, which is added to the food for its long-lasting product. At least, if the goods are not sold today, the formalized chicken or tofu is resold the next day and still looks fresh. 2. Legal arrangements for food sales agents containing hazardous substances in accordance with the laws and regulations applicable in the field of food, health, and consumer protection basically regulate the protection of the public in order to consume food in circulation to be assured of its safety, in accordance with standard and / or health requirements.food that does not meet the standards, health requirements, and / or endanger health is prohibited to be circulated, withdrawn from circulation revoked permit and seized for destruction in accordance with the provisions of legislation. 3. the application of criminal sanctions against food sellers containing hazardous materials may be subject to criminal sanctions, criminal penalties, and additional criminal charges in accordance with the offenses committed and can be proven through court hearings. through the application of criminal sanctions it is expected that the purpose of food security can be achieved in order to provide legal protection for the community.